Topical resiquimod dosing regimens in patients with multiple actinic keratoses: a multicentre, partly placebo‐controlled, double‐blind clinical trial. (22nd October 2018) - Stockfleth, E.; Hofbauer, G.F.L.; Reinhold, U.; Popp, G.; Hengge, U.R.; Szeimies, R.M.; Brüning, H.; Anliker, M.; Hunger, T.; Dummer, R.; Ulrich, C.; Kenzelmann, R.; et al.
Summary: Background: Topical immune response modifiers are established for actinic keratosis (AK) treatment and efforts are underway to make further improvements to their efficacy and safety. Objectives: To investigate the optimal dosing regimens of the Toll‐like receptor 7/8 agonist resiquimod in terms of efficacy, safety and tolerability. Methods: In a multicentre, partly placebo‐controlled, double‐blind clinical trial, we randomized 217 patients with AK lesions to 0·03% resiquimod gel once‐daily application three times per week for 4 weeks or seven times within 2 weeks or five times for 1 week (arms 1/2/3) followed by a treatment‐free interval of 8 weeks and one repetition of the cycle. In two additional arms (arms 4/5), patients applied either resiquimod gel 0·01% or 0·03% three times per week up to a biological end point defined by skin erosion or for a maximum duration of 8 weeks. Clearance was assessed clinically and histologically. Results: Complete clinical clearance ranged from 56% to 85% with the highest rate observed in arm 2. Resiquimod 0·03% gel was more effective than 0·01% gel. Clearance rates in arms 1/2/3 were comparable and higher than with placebo and were reached with 24, 14 and 10 gel applications, respectively. Overall, 128 patients (59%) experienced treatment‐related adverse reactions. Conclusions: Resiquimod 0·03% gel is more effective than 0·01% gel. From the perspectives of safety and tolerability, the lower concentration and shorter duration are preferable. The clinical response in arms 2/3 was reached with fewer gel applications. The dosing regimens that used the biological end point (arms 4/5) proved equally efficacious as predefined treatment durations and may therefore be suitable for personalized AK treatment. Abstract : What's already known about this topic? Actinic keratosis (AK) occurs in sun‐exposed skin areas and may progress to squamous cell carcinoma if left untreated. AK treatments are often lengthy and demand high levels of commitment from patients. What does this study add? Resiquimod gel at concentrations of 0·03% and 0·01% was effective for AK treatment on the balding scalp, forehead or face. A reduction in the total number of gel applications (from 24 to 10) gave comparable clearance rates and may therefore simplify AK treatments. Dosing regimens that used the biological end point of skin erosion proved to have equal levels of efficacy as the regimens that used a predefined treatment duration and may therefore be suitable for personalized AK treatment. Linked Comment: Rajaratnam. Br J Dermatol 2019; 180 :254–255 . Respond to this article